2021
DOI: 10.1055/s-0041-1730883
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Red Cell and Platelet Distribution Width in Patients of Medical Intensive Care Unit

Abstract: Introduction The red blood cell distribution width (RDW) is a measurement of variations in the size of red blood cells. As the width increases, the rate of mortality also increases, although the reason for it is still not known. On the other hand, platelet distribution width (PDW) is also useful in predicting morbidity and mortality in sepsis and other critically ill patients. In our study, we planned to study the impact of both RDW and PDW and evaluate their prognostic importance with outcome in patients admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…PDW is utilized to depict the distribution of PLT volume, and when PLT is excessively consumed, the bone marrow produces abundant immature PLT that is larger than mature PLT. PDW is also significantly associated with sepsis and other severe illnesses, which is closely linked to poor COVID-19 outcomes and death (31,32). In this study, the severe group showed a larger PDW, with a mean of 17.35 versus 16.88, which was significantly different from the non-severe group (p =0.001).…”
Section: Discussionmentioning
confidence: 55%
“…PDW is utilized to depict the distribution of PLT volume, and when PLT is excessively consumed, the bone marrow produces abundant immature PLT that is larger than mature PLT. PDW is also significantly associated with sepsis and other severe illnesses, which is closely linked to poor COVID-19 outcomes and death (31,32). In this study, the severe group showed a larger PDW, with a mean of 17.35 versus 16.88, which was significantly different from the non-severe group (p =0.001).…”
Section: Discussionmentioning
confidence: 55%
“…For the mortality time, the longest observation time published was 90 days in just one study ( 30 ), yet the shortest observation time published was 1 day ( 35 ). Eight studies ( 19 , 21 , 23 , 28 , 31 33 , 37 ) did not provide a definite mortality time and just defined it as “during ICU hospitalization” or “during hospitalization.” The characteristics of the included studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…According to which of the included studies are using the Sepsis-2 definition and which the Sepsis-3 definition, we also made a sensitivity analysis of this research, the aim of which was to investigate the stability of the results. We did sensitivity analysis using “METANINF.” Nine studies ( 13 , 19 , 22 , 25 , 28 , 29 , 31 , 35 , 36 ) that were defined as Sepsis-s and had potential influence on the results were excluded after removing the above four studies that had significantly impacted on sensitivity. The rest of the included studies were distributed between upper and lower 95% confidence intervals with the estimation line as the center.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Jawaharani et al has shown that music therapy has a better outcome in critically ill patients with sepsis [ 11 ]. One study studied red cell distribution width and PDW as significant indicators for the period of stay in the MICU, the requirement for mechanical ventilation, and mortality [ 10 ]. There are few studies conducted in India that have assessed the role of platelet indices in sepsis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have evaluated different scoring systems as well as music therapy regarding the outcomes of critically ill patients admitted to the medical intensive care unit (MICU) [7][8][9][10]. A study by Jawaharani et al has shown that music therapy has a better outcome in critically ill patients with sepsis [11].…”
Section: Introductionmentioning
confidence: 99%